Optimal Reserves in Financially Closed Economies - Jeanne, Olivier (IMF Working Papers; Working Paper ;, 2016)
Financially closed economies insure themselves against current-account shocks using international reserves. We characterize the optimal management of reserves using an open-economy model of precautionary savings and emphasize several results. First, the welfare-based opportunity cost of reserves differs from the measures often used by practitioners. Second, under plausible calibrations the model is consistent with the rule of thumb that reserves should be close to three months of imports. Third, simple linear rules can capture most of the welfare gains from optimal reserve management. Fourth, policymakers should place more emphasis on how to use reserves in response to shocks than on the reserve target itself.